ROLE OF COMMUNITY BASED EMPOWERMENT OF POOR COMMUNITIES THROUGH HOPE FAMILY PROGRAMS IN INDONESIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This study aims to analyze and describe the role of community-based companion empowerment through the PKH program in Telaga District, Gorontalo Regency. Data collection techniques used are through observation, interviews and documentation. Researchers use the method of observation because in this qualitative study, researchers must know firsthand the situation or reality of the field so that clear information can be obtained.The results showed that the companion needed time to adapt, and the difficulty of PKH participants to be on time. External factors that become obstacles are sudden information, the distance of the companion to the assistance location is quite far, and access roads that are difficult to reach. Supporting factors include support from beneficiary communities and mothers who are diligently present, and assistance tools in the form of books containing material that is very helpful in delivering Family Development Sessions (FDS).